2021
DOI: 10.1186/s12893-021-01394-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of Tightrope system in the treatment of purely ligamentous Lisfranc injuries

Abstract: Background Purely ligamentous Lisfranc injuries are mainly caused by low energy damage and often require surgical treatment. There are several operative techniques for rigid fixation to solve this problem clinically. This study evaluated the effect of using the Tightrope system to reconstruct the Lisfranc ligament for elastic fixation. Methods We retrospectively analyzed 11 cases with purely ligamentous Lisfranc injuries treated with the Tightrope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Patient-reported outcome according to the AOFAS improved from 31 at the time of injury to 90 postoperatively. Supportive data from small retrospective series including both acute 73,74 and chronic injuries 75 have been reported. Concerns regarding fixation purchase in poor-quality bone limit the indication of these implants to younger patients with purely ligamentous injuries, and there are currently no level 1 data to support use.…”
Section: Treatmentmentioning
confidence: 79%
“…Patient-reported outcome according to the AOFAS improved from 31 at the time of injury to 90 postoperatively. Supportive data from small retrospective series including both acute 73,74 and chronic injuries 75 have been reported. Concerns regarding fixation purchase in poor-quality bone limit the indication of these implants to younger patients with purely ligamentous injuries, and there are currently no level 1 data to support use.…”
Section: Treatmentmentioning
confidence: 79%
“…AOFAS scores were pooled from 6 studies, [7][8][9]11,23,35 with a mean score among 150 patients of 90.1 at a mean time of 30.7 months; this indicates an excellent result. 10 VAS scores were reported in 5 studies, 8,11,18,23,35 and among the 137 patients, the mean score was 1.5 at a time of 30.8 months; this is consistent with minimal or no pain. 17,24 Cho et al 8 found significantly inferior clinical outcomes associated with conventional screw fixation in comparison with suture button fixation.…”
Section: Clinical Resultsmentioning
confidence: 99%
“…The mean MINORS score of the 11 studies was 8.9 (range, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Open reduction was performed in 8 studies, [6][7][8][9]11,18,23,35 with 1 study 33 reporting percutaneous reduction and 2 studies 14,25 not specifying. All studies used the Mini TightRope (Arthrex) between the medial cuneiform and second metatarsal for fixation.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…14 Anatomic reconstruction of the Lisfranc ligament is a possible treatment option for acute Lisfranc ligament injury. 8,17,34 For this purpose, MRI is useful to know the condition of the Lisfranc, dorsal, and plantar ligaments in the acute phase of injury. If open reduction and screw fixation or primary arthrodesis were selected for operative management, MRI was not indicated for diagnosis of acute Lisfranc injury.…”
Section: Discussionmentioning
confidence: 99%
“…13,33 Anatomical reconstruction of the Lisfranc ligament has been developed as an alternative operative procedure for Lisfranc ligament injury. 8,17,34 Direct observation of the degree of injury of the Lisfranc ligament, the dorsal ligament, and the interosseous C1-C2 ligament is performed during surgery. 8 Precise diagnosis of these ligament injuries is important to select the best treatment option.…”
Section: Introductionmentioning
confidence: 99%